DESIGUALDADE DE RENDA NO MARANHÃO: Uma avaliação do período entre 2000 e 2010 - Silva, Leilivania Lima da (2014)
Evidences about the income inequality in Maranhão in the period between the year 2000 and 2010. It emphasizes the role of economic growth and income transfers in this process. Income inequality, in practice, is usually assessed by indicators such as the Gini index, Theil L index and the income proportions of the poorest 40% and the richest 10%. The per capita income as a variable emphasized by researchers, can be analyzed by four angles: GDP per capita, average per capita household income, income from earnings and Income Transfers. Besides income and inequality, it is made a reference to the incidence of poverty in the state, measured by personal income as a result of the level of inequality. The results point to the fact that most of the reduction in income inequality over the period was due to changes in income not derived from work, given that, although the work is the main source of household income, the share of labor income in total income declined over this period, while the share of income from cash transfers increased sharply.